PENGARUH TEKNIK ASSERTIVE TRAINING UNTUK MENINGKATKAN KEMATANGAN HUBUNGAN SOSIAL SISWA KELAS X SMAN 8 PEKANBARU - Mahrani, Uci; Yakub, Elni; Umari, Tri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the effect of assertive training techniques to improve the maturity of social relations of class X students of SMAN 8 Pekanbaru. This research was conducted at SMAN 8 Pekanbaru for 3 months. This type of research uses quantitative research with an experimental method using the One-Group Pretest-Posttest Design research design. The measuring instrument used in this study is the social relations maturity measurement scale which consists of 81 items before the validity, and after divalidity there are 47 valid items with validity of 0.344 and reliability of 0.925. Determination of the subject using purporsive sampling technique, and get the subject of 7 grade X students of SMAN 8 Pekanbaru who identified as having a low level of social relations mortality. The data analysis technique used is the non parametric statistical technique using the Wilcoxon analysis test. The results of the study proved that the research hypothesis was accepted. This is known from "Test Statistics", known as Asymp. Sig. (2-tailead) is 0.018. Because the value of 0.018 is smaller than <0.05, it can be concluded that "Ha is accepted". To that end, it can be concluded that there are differences in the maturity score of social relations before and after treatment in the form of assertive training techniques. The difference between the mean Pre-test and Post-test was 94.85. Thus Ha is accepted and Ho is rejected. So it can be concluded that the assertive training technique can improve the maturity of social relations of class X students of SMAN 8 Pekanbaru. Key Words: Assertive training, maturity of social relations.